STEM Education Implementation in Indonesia: A Scoping Review - Farwati, Ratna; Metafisika, Kartika; Sari, Indah; Sitinjak, Debora Suryani; Solikha, Dian Farkhatus; Solfarina, Solfarina (Gemilang Maju Publikasi Ilmiah (GMPI), 2021)
In Indonesia, STEM education has been implemented in the learning process since 2014. The number of researches on the implementation of STEM education are increasing from year to year. Therefore, this research was conducted to map the all articles published online with the theme of STEM education implementation in Indonesia. The scoping review was carried out following the framework from Arksey O'Malley (2005), with the following steps: (1) formulating research questions, (2) exploring research results on Google Scholar database from 2015-2020 with the keyword “implementation” +